Implementation of Group Counseling Self-Management Techniques to Reduce Student Gadget Addiction - Barida, Muya; Sari, Aprilia Puspita (citeus, 2025)
Gadget addiction as a behavior of attachment or dependence on smartphones may become a social problem such as withdrawal, and difficulties in performing daily activities or as a disorder of impulse control against oneself. The purpose of this study was to determine the effectiveness of self-management technique group counseling to reduce students' gadget addiction. The type of research used is an experiment using the one group pretest posttest design model. Subject determination by purposive sampling. The subjects of this study were students of class VIII-C at Muhammadiyah 2 Kalasan Middle School, namely 5 students. Data collected in quantitative form (numbers) were then analyzed statistically using the t-test. The research findings obtained facts about the coefficient t-count = 6.946 then compared with t-table at a significance level of 5% for dk = n–1= 5–1= 4 is 2.131. This shows that t count is greater than t table, namely 6.946 > 2.131. The conclusion of the results of this study is that self-management technique group counseling services is effective for reducing gadget addiction for class VIII-C students of Muhammadiyah 2 Kalasan Middle School.